Expanded taxonomies of human memory - Finley, Jason R. (Frontiers in Cognition, 2025)
What is human memory? Evidence from cognitive psychology and neuroscience supports the view that human memory is composed of multiple subsystems. The influential “modal model” of the late 1960s proposed a sensory register, short-term store, and long-term store. Refinements and expansions to this taxonomy followed, including the construct of working memory, itself with several components, to replace earlier simpler ideas of short-term memory. Long-term memory appears to also consist of several subsystems, which can be broadly divided into explicit (declarative) vs. implicit (nondeclarative). Explicit long-term memory can be further subdivided into episodic vs. semantic, and implicit long-term memory includes subtypes such as procedural memory, priming, classical conditioning, and habituation. All of the above take place in the human brain, driven by neurons and the processes of long-term potentiation and depression. I previously proposed an expanded taxonomy that included external memory, which is information stored outside of an individual's brain, subdivided into social (information stored in other people) and technological (information stored in the human-made environment, either low-tech such as paper, or high-tech such as computers). In this manuscript, I propose even further expanded taxonomies of human memory, based on my view that memory is the transmission of information across time. The second expansion encompasses numerous biological systems beside the brain, including the immune system, genetics (DNA and epigenetics), and traces of the past stored elsewhere in the body (skin, hair, body modification, nails, bones and teeth, muscles and movement, voice, digestion and excretion, blood, reproductive systems, fat, lungs, and body-based numerical representation). The third expansion distinguishes between individual and collective memory (shared memory of a social group), revisits the other systems using the lens of collective memory, and adds natural external memory. Fruitful insights are possible from considering these expanded taxonomies using traditional ideas from cognitive psychology (e.g., encoding, storage, retrieval, forgetting). I explore numerous parallels, distinctions, and interplays.